Brain Structure and Function in Women with Comorbid Bipolar and Premenstrual Dysphoric Disorder - Syan, Sabrina K.; Minuzzi, Luciano; Smith, Mara; Costescu, Dustin; Allega, Olivia R.; Hall, Geoffrey B. C.; Frey, Benicio N. (Frontiers in Psychiatry, 2018)
Introduction: Hormonal fluctuations associated with female reproductive life events may precipitate or worsen affective episodes in women with bipolar disorder (BD). Previous studies have shown that women with BD report higher rates of premenstrual dysphoric disorder (PMDD) than controls. Further, bipolar women who report premenstrual worsening of mood display a worse course of their bipolar illness. Despite this, the neural correlates of co-morbid BD and PMDD have not been investigated. Methodology: Eighty-five (CTRL, n=25; PMDD, n=20; BD, n=21; BDPMDD, n=19), regularly cycling women, not on hormonal contraception, underwent two MRI scans: during their mid-follicular and late luteal menstrual phases. We investigated resting-state functional connectivity (Rs-FC), cortical thickness and subcortical volumes of brain regions associated with the pathophysiology of BD and PMDD between groups, in the mid-follicular and late luteal phases of the menstrual cycle. All BD subjects were euthymic for at least two months prior to study entry. Results: Women in the BDPMDD group displayed greater disruption in biological rhythms and more subthreshold depressive and anxious symptoms through the menstrual cycle compared to other groups. Rs-FC was increased between the L-hippocampus and R-frontal cortex and decreased between the R-hippocampus and R-premotor cortex in BDPMDD vs BD (FDR-corrected, p<0.05). Cortical thickness analysis revealed decreased cortical thickness of the L-pericalcarine, L-superior parietal, R-middle temporal, R-rostral middle frontal and L-superior frontal, as well as increased cortical thickness of the L-superior temporal gyri in BDPMDD compared to BD. We also found increased left-caudate volume in BDPMDD vs BD (pcorr<0.05). Conclusions: Women with BD and co-morbid PMDD display a distinct clinical and neurobiological phenotype of BD, which suggests differential sensitivity to endogenous hormones.